Teaching approaches strategies - Salandanan, Gloria G. (Quezon City, Philippines : Katha Publishing Co, Inc., 2000)
Teaching approaches and strategies represents a modest attempt to present some models of teaching approaches and strategies that easily lead to a wide range of content across disciplines, ability levels and age groups. One of its goals is to offer a repertoire of teaching methodologies that have been tried and proved effective in different yet conducive teaching- learning environments.
I. Teaching Approaches --1. Reflective teaching -- 2. Cooperative learning approach -- 3. Experiential learning -- 4. Direct instruction -- 5. Constructivist approach -- 6. Inquiry teaching -- 7. Concept teaching -- 8. S-T-S approach -- 9. Interest learning centers -- 10. Team teaching -- II. Teaching strategies -- 11. Synoptics -- 12. Simulations -- 13. Role playing -- 14. Journal writing -- 15. Narratives -- 16. Community resources -- 17. Problem solving -- 18. Peer tutoring -- 19. Microteaching -- 20. Field studies -- 21. Experimenting -- 22. Classroom demonstration -- 23. Discussion -- 24. Student research -- 25. Independent study -- 26. Individualized instruction -- 27. Projects -- 28. Collections -- 29. Reading -- 30. Lecture
Includes bibliographical references.
Keywords: TEACHING METHODS